2022
DOI: 10.3389/fonc.2022.951976
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and renal cancers: A bidirectional association

Abstract: There is a deep interrelation between the thyroid gland and the kidney parenchyma, with dysfunction of the first leading to significant changes in renal metabolism and vice versa. Given the recognition of cancer as a systemic disease, the raise of thyroid tumors and the common association of several malignancies, such as breast cancer, prostate cancer, colorectal cancer, and other, with an increased risk of kidney disease, public health alert for these conditions is warranted. A systematic review of the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…Hence, the male sex is seen as a risk factor for the association of these cancers. Even though exposure to radiation is a well-known risk factor for cancer development in general and particularly for thyroid cancers, Bellini et al did not find any association between radiotherapy and the development of renal and thyroid cancers [17]. Our case did not have a history of radiation exposure.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Hence, the male sex is seen as a risk factor for the association of these cancers. Even though exposure to radiation is a well-known risk factor for cancer development in general and particularly for thyroid cancers, Bellini et al did not find any association between radiotherapy and the development of renal and thyroid cancers [17]. Our case did not have a history of radiation exposure.…”
Section: Discussioncontrasting
confidence: 62%
“…They identified family history and obesity as common shared risk factors, and genetic susceptibility as a strong contributor to both cancers. They found that after a thyroid cancer, men were more likely to develop renal cancer [17]. According to a study by Van Fossen et al, female patients with thyroid cancer were nearly two times more likely to develop a subsequent renal carcinoma, and the risk was 4.5-folds in men.…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid gland and kidney have a well-known interrelationship. The thyroid gland is necessary for renal cell growth and maintenance of hydro-electrolyte homeostasis (9). On the other hand, the kidney is responsible for elimination of thyroid hormones and regulation of their serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors connecting the thyroid gland and kidney have been studied to hypothesize why tumors spread preferentially between the two organ systems. Speci c risk factors include obesity, family history, male sex and increasing age and these are shown to increase the risk of both cancers (9).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid diseases (TDs) have been associated with the occurrence of a number of extra-thyroidal malignancies (EM), including colorectal cancers (CRCs) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. These associations have generated a great interest based on the opportunity to detect possible shared congenital and environmental elements liable for diseases’ etiology and/or progression.…”
Section: Introductionmentioning
confidence: 99%